A compact ultra‐wideband receiving antenna for monitoring applications. Issue 1 (1st October 2021) - Zhang, Ying; Chen, Xin; Yao, Jiaqi; Yang, Jizhong; Mao, Zhiming; Hua, Yifeng
Abstract: In this paper, a compact ultra‐wideband receiving antenna is proposed. It consists of a top loaded planar monopole and a circular ground plane. This design combines various techniques such as the comb shaped top loading and the integrated lumped elements to effectively reduce the antenna size, while keeping a wide bandwidth and a reasonable realized gain. The proposed antenna operates across a wide frequency range from 20 to 8 GHz (for S 11 <−6 dB), occupies a compact volume of 500 × 500 × 340 mm 3 (0.033 λ 0 × 0.033 λ 0 × 0.023 λ 0 at 20 MHz) and has a stable omnidirectional radiation pattern in azimuth plane from 20 to 6 GHz. Simulations and measurements are conducted to validate the antenna performance. It is demonstrated that this antenna is well suited to a variety of wideband radio frequency receivers for monitoring use.